Treatment of dentin hypersensitivity in non-carious cervical lesions: a review of the literature (Research, Society and Development, 2021)
Dentin hypersensitivity (HD) can be defined as a pathological process that has a multifactorial etiology and depends on stimuli in exposed dentinal tubules supragingivally, subgingivally and below structural defects and enamel cracks that can trigger a pain of acute and short-lived symptomatology. According to the hydrodynamic theory, HD is the result of fluid flow in the dentin tubules. It is commonly associated with non-carious cervical lesions and factors such as tension, friction and biocorrosion, which may act alone or in combination. This paper reviewed the literature regarding treatments for HD in non-carious cervical lesions. It was possible to find in the scientific literature several techniques of therapeutic resources to reduce the symptoms of HD. However, the application of these resources should be initiated after a thorough clinical and differential diagnosis associated with an extra-oral physical examination, intra-oral clinical examination and detailed radiographic examination, differentiating HD from other pathologies. The objective of the treatments is to identify and control the causal factors, the ideal material for dentin hypersensitivity treatment must be biocompatible, easy to apply, have a long-lasting, permanent and fast-acting effect, not be a pulp irritant, and not alter the color of the tooth structure. A combination of oral hygiene instruction, use of home desensitizers, and treatments performed in the dental office, including professional use desensitizers and restorative treatments, are able to decrease and eliminate dentin hypersensitivity.